Did Jesus want to be remembered? - Hardie, Adam (2017)
This study will evaluate as to whether the Historical Jesus wanted to be remembered. In addition - if Jesus wanted to be remembered - we will also examine how Jesus’ method to preserve his memory compared with other ancient figures. This investigation will propose that Jesus wanted his life to be remembered, using similar methods to how God demonstrated that he wanted to be remembered in the Old Testament.